Strategies of women SMEs actors in advancing the Laweyan batik business: The analytic hierarchy process method - Prasetyani, Dwi; Juwita, Aulia Hapsari; Wiyono, Vincentius Hadi; Bintariningtyas, Selfia; Indriawati, Ratna Malisa (International Journal of Innovative Research and Scientific Studies, 2025)
The COVID-19 pandemic poses unprecedented challenges for SMEs, particularly in technology adoption and workforce management. This study explores post-COVID-19 recovery strategies for Batik Laweyan women SMEs, focusing on business preferences and technology integration. The research was conducted by utilizing the Analytical Hierarchy Process (AHP) method, which prioritizes the main areas for development: information technology, financial capital, and labor quality. Women SME actors in the batik fashion business are the subjects of this study. The findings show that the ability of women SMEs in the Batik industry is more focused on gaining helpful knowledge related to access to business financing, taking advantage of opportunities, building networks with technology, and solving problems efficiently. This study provides valuable insights for policymakers and businesspeople who aim to support the development of women SMEs and improve the sustainability of Laweyan Batik SMEs in the post-COVID-19 pandemic.